Minimally invasive versus open distal pancreatectomy for pancreatic neuroendocrine tumors: An analysis from the U.S. neuroendocrine tumor study group. Issue 2 (18th April 2019) - Zhang, Xu‐Feng; Lopez‐Aguiar, Alexandra G.; Poultsides, George; Makris, Eleftherios; Rocha, Flavio; Kanji, Zaheer; Weber, Sharon; Fields, Ryan; Krasnick, Bradley A.; Idrees, Kamran; Smith, Paula M.; Cho, Cliff; et al.
Abstract: Background: To determine short‐ and long‐term oncologic outcomes after minimally invasive distal pancreatectomy (MIDP) with open distal pancreatectomy (ODP) for the treatment of pancreatic neuroendocrine tumor (pNET). Methods: The data of the patients who underwent curative MIDP or ODP for pNET between 2000 and 2016 were collected from a multi‐institutional database. Propensity score matching (PSM) was used to generate 1:1 matched patients with MIDP and ODP. Results: A total of 576 patients undergoing curative DP for pNET were included. Two hundred and fourteen (37.2%) patients underwent MIDP, whereas 362 (62.8%) underwent ODP. MIDP was increasingly performed over time (2000‐2004: 9.3% vs 2013‐2016: 54.8%; P  < 0.01). In the matched cohort (n = 141 in each group), patients who underwent MIDP had less blood loss (median, 100 vs 200 mL, P  < 0.001), lower incidence of Clavien‐Dindo ≥ III complications (12.1% vs 24.8%, P  = 0.026), and a shorter hospital stay versus ODP (median, 4 versus 7 days, P  = 0.026). Patients who underwent MIDP had a lower incidence of recurrence (5‐year cumulative recurrence, 10.1% vs 31.1%, P  < 0.001), yet equivalent overall survival (OS) rate (5‐year OS, 92.1% vs 90.9%, P  = 0.550) compared with patients who underwent OPD. Conclusion: Patients undergoing MIDP over ODP in the treatment of pNET had comparable oncologic surgical metrics, as well as similar long‐term OS.